Polyglycolic acid composite material as well as preparation method and application thereof

By blending and modifying PGA with PBC and introducing PLA, the problems of insufficient toughness and blown film processing performance of PGA are solved, and the problem of poor opening properties caused by slow crystallization of PBC is solved through the rapid crystallization and good compatibility of PLA, thereby achieving a fully biodegradable composite material with high toughness and good processing performance.

CN119875334AActive Publication Date: 2025-04-25CHINA SHENHUA COAL TO LIQUID & CHEM CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510131872.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-06
Publication Date
2025-04-25
Estimated Expiration
2045-02-06

AI Technical Summary

Technical Problem

In applications, polyglycolic acid (PGA) has poor toughness, low melt strength, difficulty in blowing the film and short shelf life, and the slow crystallization speed of polybutylene carbonate (PBC) leads to poor opening of the film.

Method used

The toughness and blowable film processability of the composite material are improved by blending and modifying PGA with PBC and introducing polylactic acid (PLA). The fast crystallization speed and good compatibility of PLA help solve the problem of poor opening properties caused by slow crystallization of PBC.

Benefits of technology

High toughness, good film blowing processing performance and opening performance have been achieved, and a fully biodegradable composite material is prepared, suitable for green packaging, biomaterials and consumer products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a polyglycolic acid composite material and a preparation method and application thereof, the polyglycolic acid composite material comprises PGA, PBC, PLA, talcum powder and an additive; wherein the polymerization degrees n of the PGA, PBC and PLA structural units are all greater than 300; based on the total mass of the PGA, the PBC and the PLA, the mass content of the PGA is 5-90%, the mass content of the PBC is 5-90%, and the mass content of the PLA is 5-90%. According to the composite material provided by the invention, the full-biodegradable composite material which is high in toughness and can be subjected to film blowing processing is prepared through blending modification, and the full-biodegradable composite material has the advantages of being high in toughness, good in film blowing processability, good in opening property, excellent in performance, simple and convenient in method and low in follow-up industrialization difficulty.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of polyglycolic acid composite materials, and relates to a polyglycolic acid composite material and a preparation method and application thereof, and in particular to a polyglycolic acid / polybutylene carbonate / polylactic acid composite material with excellent comprehensive performance and a preparation method and application thereof. Background Art

[0002] Polyglycolic acid (PGA) is a biodegradable, highly crystalline aliphatic polyester. Due to its outstanding crystallinity and segment structure characteristics, it has excellent mechanical properties, gas barrier properties and biocompatibility, so it is widely used in the fields of biomedicine and ecology. However, PGA also has shortcomings, such as poor product toughness, low melt strength, difficulty in film blowing, and short shelf life of products, which limit its large-scale expansion and application, and need in-depth research to solve them.

[0003] Polybutylene carbonate (PBC) is also an important biodegradable polymer material with the characteristics of moderate biodegradation rate, excellent toughness and good biocompatibility. In addition, its structure is adjustable, the product color is good, the catalyst usage is small, and the polymerization process is simple, so it has good industrial prospects. The thermodynamic and mechanical properties of aliphatic polycarbonate and PGA are naturally complementary. Blending and modifying PGA with aliphatic polycarbonate is an effective way to solve the above-mentioned problems of PGA. However, the crystallization rate of PBC is slow, which makes it easy to stick and difficult to open during film blowing, which limits its convenience in large-scale film blowing production. However, the degree of improvement in the crystallization rate of PBC using nucleating agents or opening agents cannot meet the requirements of opening during film blowing, so this is also a problem that needs to be studied and solved.

[0004] Polylactic acid (PLA) is a new type of biodegradable material, made from starch raw materials from renewable plant resources (such as corn), and is a recognized environmentally friendly material. It has good mechanical and physical properties. Polylactic acid is suitable for various processing methods such as blow molding and thermoplastics. It is easy to process and has a wide range of applications. Polylactic acid has a faster crystallization rate and good compatibility with PBC, so it can be used as a modifier to improve the opening performance of PGA / PBC composite materials during film blowing. Summary of the invention

[0005] In view of the problems existing in the prior art, the object of the present invention is to provide a polyglycolic acid composite material and a preparation method and application thereof, so as to improve the high toughness and blown film processability of the polyglycolic acid composite material.

[0006] To achieve one aspect of the above-mentioned object of the invention, the polyglycolic acid composite material provided by the present invention adopts the following technical solution:

[0007] A polyglycolic acid composite material, a polyglycolic acid composite material comprising PGA, PBC, PLA, talc and additives;

[0008] Among them, the structures of PGA, PBC and PLA are shown in the following formula I, the following formula II and the following formula III respectively:

[0009]

[0010] Among them, the polymerization degree n of the PGA, PBC and PLA structural units is greater than 300;

[0011] Wherein, based on the total mass of PGA, PBC and PLA, the mass content of PGA is 5-90%, the mass content of PBC is 5-90%, and the mass content of PLA is 5-90%.

[0012] To achieve another aspect of the above-mentioned object of the invention, the present invention provides a method for preparing the above-mentioned polyglycolic acid composite material, comprising the following steps:

[0013] S1: mixing PGA, PBC, PLA, talc and additives to obtain a mixture;

[0014] S2: Melting the mixture and extruding and granulating it to obtain the polyglycolic acid composite material.

[0015] In order to achieve another aspect of the above-mentioned invention object, the present invention provides the use of the polyglycolic acid composite material as a film material and an injection molding material.

[0016] In the present invention, unless otherwise specified, all ratios or percentages involved are mass ratios or mass percentages.

[0017] Compared with the prior art, the present invention has the following advantages:

[0018] The composite material provided by the present invention improves the toughness and processing performance of PGA by blending and modifying PGA and PBC, and adjusts its degradation rate, thereby realizing continuous film blowing processing; in addition, in view of the fact that a nucleating agent or an opening agent cannot effectively solve the problem of poor opening of the blend, PLA is added, and the characteristics of PLA's fast crystallization rate and good compatibility with PBC are utilized to solve the problem of poor opening of PGA / PBC due to the slow crystallization rate of PBC. A highly tough, film-blowable fully biodegradable composite material is prepared. The blend prepared by the method described in the present invention has the advantages of high toughness, good film blowing processability, good opening, excellent performance, simple method and low difficulty in subsequent industrialization. DETAILED DESCRIPTION

[0019] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0020] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values, such as values ​​of ±10% of the endpoint values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. In the absence of conflict, the embodiments in this application and the features in the embodiments can be combined with each other.

[0021] It should be noted that the terms "include" and "have" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or apparatus comprising a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to these processes, methods, products or apparatus.

[0022] The polyglycolic acid composite material of the present invention comprises polyglycolic acid (PGA), polybutylene carbonate (PBC), polylactic acid (PLA), talcum powder and additives; the additives comprise a heat stabilizer, an antioxidant, an anti-blocking agent and a chain extender;

[0023] Among them, the structures of PGA, PBC and PLA are shown in the following formula I, the following formula II and the following formula III respectively:

[0024]

[0025] Among them, the polymerization degree n of the PGA, PBC and PLA structural units is greater than 300;

[0026] Wherein, based on the total mass of PGA, PBC and PLA, the mass content of PGA is 5-90%, the mass content of PBC is 5-90%, and the mass content of PLA is 5-90%.

[0027] In one embodiment, the talc is added in an amount of 2-30% of the total mass of PGA, PBC and PLA, such as 2%, 5%, 8%, 11%, 14%, 17%, 20%, 23%, 26%, 30%, preferably 2-10%.

[0028] In the present invention, based on the total mass of PGA, PBC and PLA, the mass content of PGA can be 5-90%, for example, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, preferably 10-40%.

[0029] In one embodiment, the melt index of PGA is less than 40 g / 10 min (230° C., 2.16 kg), preferably less than or equal to 20 g / 10 min (230° C., 2.16 kg). The melt index of PGA can be 10 to 20 g / 10 min. For example, 10 g / 10 min, 12 g / 10 min, 15 g / 10 min, 16 g / 10 min, 18 g / 10 min, 20 g / 10 min.

[0030] In the present invention, the degree of polymerization of the repeating unit of PGA is greater than 300, preferably 300-600, such as 400 or 500.

[0031] In the present invention, based on the total mass of PGA, PBC and PLA, the mass content of PBC can be 5 to 90%, for example, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, preferably 10-80%.

[0032] In one embodiment, the melt index of PBC is less than 20 g / 10 min (150° C., 2.16 kg), preferably less than 10 g / 10 min (150° C., 2.16 kg). The melt index of PBC can be 0.7 to 6 g / 10 min. For example, 0.7 g / 10 min, 1.5 g / 10 min, 1.8 g / 10 min, 2 g / 10 min, 3 g / 10 min, 4 g / 10 min, 5 g / 10 min, 6 g / 10 min.

[0033] In the present invention, the degree of polymerization of the repeating unit of PBC is greater than 300, preferably 300-600, such as 400 or 500.

[0034] In the present invention, based on the total mass of PGA, PBC and PLA, the mass content of PLA can be 5 to 90%, for example, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, preferably 10-60%.

[0035] In one embodiment, the melt index of PLA is less than 20 g / 10 min (190° C., 2.16 kg), preferably less than 10 g / 10 min (190° C., 2.16 kg). The melt index of PLA can be 0.7 to 6 g / 10 min. For example, 0.7 g / 10 min, 1.5 g / 10 min, 1.8 g / 10 min, 2 g / 10 min, 3 g / 10 min, 4 g / 10 min, 5 g / 10 min, 6 g / 10 min.

[0036] In the present invention, the degree of polymerization of the repeating unit of PLA is greater than 300, preferably 300-600, such as 400 or 500.

[0037] In one embodiment, the additive includes one, two or more of a heat stabilizer, an antioxidant, an opener and a chain extender.

[0038] In one embodiment, based on the total mass of PGA, PBC and PLA, the mass content of the heat stabilizer can be 0.01-3%, for example, 0.05%, 0.08%, 0.1%, 0.2%, 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%; preferably, the mass content of the heat stabilizer can be 0.05-1%.

[0039] In one embodiment, based on the total mass of PGA, PBC and PLA, the mass content of the antioxidant can be 0.01-3%, for example, 0.05%, 0.08%, 0.1%, 0.15%, 0.2%, 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%; preferably, the mass content of the antioxidant can be 0.05-1%.

[0040] In one embodiment, based on the total mass of PGA, PBC and PLA, the mass content of the opening agent can be 0.01-3%, for example, 0.05%, 0.08%, 0.1%, 0.2%, 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%; preferably, the mass content of the opening agent can be 0.05-1%.

[0041] In one embodiment, based on the total mass of PGA, PBC and PLA, the mass content of the chain extender can be 0.01-5%, for example, 0.05%, 0.08%, 0.1%, 0.2%, 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%; preferably, the mass content of the chain extender can be 0.1-2%.

[0042] In one embodiment, the heat stabilizer may be at least one of phosphite heat stabilizers, preferably one or more of triphenyl phosphite, trimethyl phosphite, and ethyl phosphite.

[0043] In one embodiment, the antioxidant may be a hindered phenol antioxidant, for example, the antioxidant may be one or more of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol ester, N,N-1,6-hexylene-bis-[3,5-di-tert-butyl-4-hydroxyphenylpropionamide], and N,N-bis[β(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine.

[0044] In one embodiment, the opening agent may be oleamide and / or erucamide.

[0045] In one embodiment, the chain extender can be one or more of diepoxide, dioximidazole, diisocyanate, polycarbodiimide, bisphthalimide, carboxylic anhydride, bicyclic imine ester, organosilazane, peroxide and diacyl dilactam; preferably, the chain extender can be N, N-diepoxypropylbenzamide, hexamethylene diisocyanate, 1,2,4,5-benzene tetracarboxylic dianhydride, phthalic anhydride, succinic anhydride, hexaphenyltrisilazane and N, N-oxalyl dicaprolactam, toluene diisocyanate, diphenylmethane diisocyanate One or more of esters, polymerized diphenylmethane diisocyanate, methylenebis(4-cyclohexyl isocyanate), dicyclohexylmethane-4-4-diisocyanate, 2,2,4-trimethylhexane diisocyanate, bis(phthalimide), benzoyl peroxide, diisopropyl peroxide, dibutyl peroxide, α,α-bis(tert-butylperoxy)diisopropylbenzene, 1,2,4,5-benzenetetracarboxylic dianhydride, bis(dioxazolone) or bis(benzoxazine), octamethylcyclotetrasilazane, hexaphenyltrisilazane 2,2-bis(2-dioxazoline).

[0046] The present invention also provides a method for preparing the above-mentioned PGA / PBC / PLA material, comprising the following steps:

[0047] S1: mixing PGA, PBC, PLA, talc and additives to obtain a mixture;

[0048] S2: Melting the mixture and extruding it into granules to obtain a PGA / PBC / PLA material.

[0049] In one embodiment, in step S2, the mixture may be melt-blended and extruded by a twin-screw extruder.

[0050] In one embodiment, the temperature of the twin-screw extruder can be 190-250°C, preferably 210-240°C, for example 230°C; the rotation speed can be 30-500r / min, preferably 70-200r / min, for example 90r / min, 100r / min, 120r / min, 150r / min, 160r / min, 180r / min, 190r / min.

[0051] The present invention prepares a toughened and degradable PGA / PBC / PLA blended composite material by a blending and modification method, which solves the shortcomings of poor toughness, low melt strength, difficulty in film blowing, and short shelf life of PGA; and at the same time solves the problem of poor opening of the blend after film blowing. The blend prepared by the method described in the present invention has the advantages of good toughness, good processing performance, good opening performance, simple operation, etc., and shows potential application prospects in green packaging, biomaterials, consumer products, building materials, etc.

[0052] The following is a further description of the PGA / PBC / PLA material and its preparation according to an embodiment of the present invention in conjunction with an example. The performance parameters in each example and comparative example are measured according to the following method:

[0053] 1. Melt index

[0054] 5 g of the PGA / PBC / PLA composition was placed in the cavity of a melt index tester, and the melt index was measured at 230° C., 2.16 kg temperature and pressure according to the test standard GB / T3682-2000.

[0055] 2. Degradation rate

[0056] Add 10 ml of water and 2 g of the sample film of the material to be tested into a sealed container, place it in a constant temperature and humidity chamber at 37°C for 30 days, dry it, weigh it, and get the undegraded mass. Degradation rate = (2-undegraded mass) / 2*100%.

[0057] 3. Elongation at break

[0058] The test was carried out on a universal tester (Instron 1122, UK) according to standard ISO527 (2012), with a sample size of 80×4×2 mm. During the test, the moving speed of the fixture beam was 20 mm / min.

[0059] In the following examples / comparative examples, unless otherwise specified, all reagents used were of analytical grade.

[0060] Example 1

[0061] S1: 10 kg PGA (melt index is 19 g / 10 min (230°C, 2.16 kg)), 80 kg PBC (melt index is 4 g / 10 min (150°C, 2.16 kg)), 10 kg PLA (melt index is 4 g / 10 min (190°C, 2.16 kg)), 0.2 kg pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 0.1 kg trimethyl phosphite, 0.2 kg oleic acid amide, 0.4 kg diphenylmethane diisocyanate, and 5 kg talc are mixed uniformly to obtain a blend.

[0062] S2: Add the uniformly mixed blend into a twin-screw extruder, set the extruder temperature to 232°C, the speed to 80r / min, extrude and granulate the blend to obtain PGA / PBC / PLA material, and perform film blowing. The PGA / PBC / PLA material was characterized according to the above method, and its melt index was 14g / 10min (230°C, 2.16kg), the elongation at break was 349%, and the degradation rate was 28%. The formula can be continuously blown film processed, and the opening performance is excellent.

[0063] Example 2

[0064] S1: 10 kg PGA (melt index is 19 g / 10 min (230°C, 2.16 kg)), 70 kg PBC (melt index is 4 g / 10 min (150°C, 2.16 kg)), 20 kg PLA (melt index is 5 g / 10 min (190°C, 2.16 kg)), 0.1 kg pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 0.2 kg triphenyl phosphite, 0.1 kg erucamide, 1 kg succinic anhydride, and 8 kg talc are mixed uniformly to obtain a blend.

[0065] S2: Add the mixed blend into a twin-screw extruder, set the extruder temperature to 228°C, the speed to 90r / min, extrude and granulate the blend to obtain PGA / PBC / PLA material, and perform film blowing. The PGA / PBC / PLA material was characterized according to the above method, and its melt index was 15g / 10min (230°C, 2.16kg), the elongation at break was 285%, and the degradation rate was 36%. The formula can be continuously blown film processed, and the opening performance is excellent.

[0066] Example 3

[0067] S1: 10kgPGA (melt index is 17g / 10min (230℃, 2.16kg)), 60kgPBC (melt index is 5g / 10min (150℃, 2.16kg)), 30kgPLA (melt index is 3g / 10min (190℃, 2.16kg)), 0.15kgN,N-1,6-hexylene-bis-[3,5-di-tert-butyl-4-hydroxyphenylpropionamide], 0.15kgtriphenyl phosphite, 0.3kgerucic acid amide, 1.4kgtoluene diisocyanate, and 6kgtalc are mixed uniformly to obtain a blend.

[0068] S2: Add the uniformly mixed blend into a twin-screw extruder, set the extruder temperature to 238°C, the speed to 110r / min, extrude and granulate the blend to obtain PGA / PBC / PLA material, and perform film blowing. The PGA / PBC / PLA material was characterized according to the above method, and its melt index was 15g / 10min (230°C, 2.16kg), the elongation at break was 208%, and the degradation rate was 47%. The formula can be continuously blown film processed, and the opening performance is excellent.

[0069] Example 4

[0070] S1: 40 kg PGA (melt index is 18 g / 10 min (230°C, 2.16 kg)), 50 kg PBC (melt index is 3 g / 10 min (150°C, 2.16 kg)), 10 kg PLA (melt index is 4 g / 10 min (190°C, 2.16 kg)), 0.1 kg N, N-1, 6-hexylene-bis-[3, 5-di-tert-butyl-4-hydroxyphenylpropionamide], 0.2 kg triethyl phosphite, 0.14 kg oleic acid amide, 1.4 kg 1,2,4,5-benzenetetracarboxylic dianhydride, and 7 kg talc are mixed uniformly to obtain a blend.

[0071] S2: Add the mixed blend into a twin-screw extruder, set the extruder temperature to 232°C, the speed to 80r / min, extrude and granulate the blend to obtain PGA / PBC / PLA material, and perform film blowing. The PGA / PBC / PLA material was characterized according to the above method, and its melt index was 17g / 10min (230°C, 2.16kg), the elongation at break was 170%, and the degradation rate was 51%. The formula can be continuously blown film processed, and the opening performance is excellent.

[0072] Example 5

[0073] S1: 30 kg PGA (melt index is 17 g / 10 min (230°C, 2.16 kg)), 40 kg PBC (melt index is 2 g / 10 min (150°C, 2.16 kg)), 30 kg PLA (melt index is 4 g / 10 min (190°C, 2.16 kg)), 0.15 kg N, N-1, 6-hexylene-di-[3, 5-di-tert-butyl-4-hydroxyphenylpropionamide], 0.2 kg triphenyl phosphite, 0.3 kg oleic acid amide, 1 kg dioxazolone, and 3 kg talc are mixed uniformly to obtain a blend.

[0074] S2: Add the uniformly mixed blend into a twin-screw extruder, set the extruder temperature to 234°C, the speed to 95r / min, extrude and granulate the blend to obtain PGA / PBC / PLA material, and perform film blowing processing. The PGA / PBC / PLA material was characterized according to the above method, and its melt index was 13g / 10min (230°C, 2.16kg), the elongation at break was 150%, and the degradation rate was 60%. The formula can be continuously blown film processed, and the opening performance is excellent.

[0075] Example 6

[0076] S1: 20 kg PGA (melt index is 17 g / 10 min (230°C, 2.16 kg)), 30 kg PBC (melt index is 1 g / 10 min (150°C, 2.16 kg)), 50 kg PLA (melt index is 2 g / 10 min (190°C, 2.16 kg)), 0.14 kg N, N-bis [β (3, 5-di-tert-butyl-4-hydroxyphenyl) propionyl] hydrazine, 0.22 kg triphenyl phosphite, 0.1 kg erucamide, 1 kg octamethylcyclotetrasilazane, and 4 kg talc are mixed uniformly to obtain a blend.

[0077] S2: Add the uniformly mixed blend into a twin-screw extruder, set the extruder temperature to 227°C, the speed to 80r / min, extrude and granulate the blend to obtain PGA / PBC / PLA material, and perform film blowing. The PGA / PBC / PLA material was characterized according to the above method, and its melt index was 12g / 10min (230°C, 2.16kg), the elongation at break was 147%, and the degradation rate was 63%. The formula can be continuously blown film processed, and the opening performance is excellent.

[0078] Example 7

[0079] S1: 30 kg PGA (melt index is 14 g / 10 min (230°C, 2.16 kg)), 20 kg PBC (melt index is 4 g / 10 min (150°C, 2.16 kg)), 50 kg PLA (melt index is 4 g / 10 min (190°C, 2.16 kg)), 0.3 kg N, N-1, 6-hexylene-di-[3, 5-di-tert-butyl-4-hydroxyphenylpropionamide], 0.12 kg triphenyl phosphite, 0.2 kg oleic acid amide, 1.5 kg α, α-bis (tert-butylperoxy) diisopropylbenzene, and 9 kg talc are mixed uniformly to obtain a blend.

[0080] S2: Add the mixed blend into a twin-screw extruder, set the extruder temperature to 235°C, the speed to 100r / min, extrude and granulate the blend, PGA / PBC / PLA material, and perform film blowing. The PGA / PBC / PLA material was characterized according to the above method, and its melt index was 14g / 10min (230°C, 2.16kg), the elongation at break was 123%, and the degradation rate was 67%. The formula can be continuously blown film processed, and the opening performance is excellent.

[0081] Example 8

[0082] S1: 30 kg PGA (melt index is 13 g / 10 min (230°C, 2.16 kg)), 10 kg PBC (melt index is 1.7 g / 10 min (150°C, 2.16 kg)), 60 g PLA (melt index is 4 g / 10 min (190°C, 2.16 kg)), 0.15 kg N, N-1, 6-hexylene-bis-[3, 5-di-tert-butyl-4-hydroxyphenylpropionamide], 0.13 kg trimethyl phosphite, 0.3 kg erucic acid amide, 0.9 kg hexamethylene diisocyanate, and 6 kg talc are mixed uniformly to obtain a blend.

[0083] S2: Add the uniformly mixed blend into a twin-screw extruder, set the extruder temperature to 237°C, the speed to 150r / min, extrude and granulate the blend to obtain PGA / PBC / PLA material, and perform film blowing. The PGA / PBC / PLA material was characterized according to the above method, and its melt index was 11g / 10min (230°C, 2.16kg), the elongation at break was 108%, and the degradation rate was 74%. The formula can be continuously blown film processed, and the opening performance is excellent.

[0084] Comparative Example 1

[0085] S1: 100 kg PGA, 0.2 kg N,N-1,6-hexamethylene-bis-[3,5-di-tert-butyl-4-hydroxyphenylpropionamide], 0.12 kg trimethyl phosphite, 0.3 kg erucic acid amide, 0.8 kg hexamethylene diisocyanate, and 6 kg talc were mixed uniformly to obtain a blend.

[0086] S2: Add the mixed blend into a twin-screw extruder, set the extruder temperature to 235°C, the speed to 150r / min, extrude and granulate the blend, and perform film blowing. The PGA sample was characterized according to the above method, and its melt index was 17g / 10min (230°C, 2.16kg), the elongation at break was 4%, the degradation rate was 100%, and the sample could not be continuously blown.

[0087] Comparative Example 2

[0088] S1: 100 kg of PBC, 0.1 kg of N,N-1,6-hexamethylene-bis-[3,5-di-tert-butyl-4-hydroxyphenylpropionamide], 0.15 kg of triphenyl phosphite, 0.14 kg of oleic acid amide, 1.2 kg of α,α-bis(tert-butylperoxy)diisopropylbenzene, and 9 kg of talc were uniformly mixed to obtain a blend.

[0089] S2: Add the mixed blend into a twin-screw extruder, set the extruder temperature to 235°C, and the speed to 90r / min, and extrude the blend into pellets. The PBC sample was characterized according to the above method, and its melt index was 2g / 10min (150°C, 2.16kg), the elongation at break was 395%, the degradation rate was 10%, and the sample could not be blown into film continuously.

[0090] Comparative Example 3

[0091] S1: 100 kg PLA, 0.1 kg N,N-1,6-hexamethylene-bis-[3,5-di-tert-butyl-4-hydroxyphenylpropionamide], 0.15 kg triphenyl phosphite, 0.14 kg oleic acid amide, 1.2 kg α,α-bis(tert-butylperoxy)diisopropylbenzene, and 9 kg talc were mixed uniformly to obtain a blend.

[0092] S2: Add the mixed blend into a twin-screw extruder, set the extruder temperature to 235°C, and the speed to 90r / min, and extrude the blend into pellets. The PLA sample was characterized according to the above method, and its melt index was 4g / 10min (190°C, 2.16kg), the elongation at break was 395%, the degradation rate was 10%, and the sample could not be blown film continuously.

[0093] Comparative Example 4

[0094] S1: 50 kg PGA, 50 kg PBC, 0.1 kg N, N-1, 6-hexylene-di-[3, 5-di-tert-butyl-4-hydroxyphenylpropionamide], 0.15 kg triphenyl phosphite, 0.14 kg oleic acid amide, 1.2 kg α, α-bis (tert-butylperoxy) diisopropylbenzene, and 9 kg talc were mixed to obtain a blend.

[0095] S2: Add the mixed blend into a twin-screw extruder, set the extruder temperature to 235°C, and the speed to 90r / min, and extrude the blend into pellets. Characterize the PGA / PBC sample according to the above method, and its melt index is 5g / 10min (190°C, 2.16kg), the elongation at break is 160%, the degradation rate is 55%, the sample can be continuously blown, and the sample cannot be opened.

[0096] Comparative Example 5

[0097] S1: 50 kg PGA, 50 kg PLA, 0.1 kg N, N-1, 6-hexylene-di-[3, 5-di-tert-butyl-4-hydroxyphenylpropionamide], 0.15 kg triphenyl phosphite, 0.14 kg oleic acid amide, 1.2 kg α, α-bis (tert-butylperoxy) diisopropylbenzene, and 9 kg talc were mixed to obtain a blend.

[0098] S2: Add the mixed blend into a twin-screw extruder, set the extruder temperature to 235°C, and the speed to 90r / min, and extrude the blend into pellets. The PGA / PLA sample was characterized according to the above method, and its melt index was 3.5g / 10min (190°C, 2.16kg), the elongation at break was 6%, the degradation rate was 70%, and the sample could not be blown film continuously.

[0099] Table 1 Performance test results of various examples and comparative examples

[0100]

[0101]

[0102]

[0103] According to the above description and the results of Table 1, the elongation at break of the material of Comparative Example 1 is 4%, the melt index of the material of Comparative Example 2 is 2g / 10min, and the elongation at break of the material of Comparative Example 3 is 8%, and both properties are obviously insufficient. The elongation at break and the melt index of the materials of Examples 1-8 are significantly improved compared with the materials of Comparative Examples 1 and 2, indicating that the problem of low toughness of PGA and inability to blow film can be solved by blending PGA with PBC, and the problem of slow crystallization of PBC causing the film to be unable to open can be solved by introducing PLA. And as the content of PBC in the example materials increases, the elongation at break of the materials increases accordingly, and the degradation rate decreases accordingly in the same time period, achieving the purpose of improving the degradation speed and toughness of the materials.

[0104] Unless otherwise defined, the terms used in the present invention have the meanings commonly understood by those skilled in the art.

[0105] Obviously, the present invention is not limited to the above embodiments, and many variations are possible. All variations that can be directly derived or associated with the contents disclosed by a person skilled in the art should be considered as falling within the protection scope of the present invention.

Claims

1. A polyglycolic acid composite material comprising PGA, PBC, PLA, talc and additives; in, The structures of PGA, PBC and PLA are shown in the following formulas Ⅰ, Ⅱ and Ⅲ respectively: Among them, the polymerization degree n of the PGA, PBC and PLA structural units is greater than 300; Wherein, based on the total mass of PGA, PBC and PLA, the mass content of PGA is 5-90%, the mass content of PBC is 5-90%, and the mass content of PLA is 5-90%.

2. The polyglycolic acid composite material according to claim 1, characterized in that: The addition amount of talc is 2-30% of the total mass of PGA, PBC and PLA, preferably 2-10%.

3. The polyglycolic acid composite material according to claim 1, characterized in that: Based on the total mass of PGA, PBC and PLA, the mass content of PGA is 10-40%, the mass content of PBC is 10-80%, and the mass content of PLA is 10-60%.

4. The polyglycolic acid composite material according to claim 1, characterized in that: The melt index of PGA is less than 40 g / 10 min (230° C., 2.16 kg), preferably 10 to 20 g / 10 min; The degree of polymerization of the repeating unit of PGA is 300-600.

5. The polyglycolic acid composite material according to claim 1, characterized in that: The melt index of PBC is less than 20 g / 10 min (150°C, 2.16 kg), preferably 0.7 to 6 g / 10 min; The degree of polymerization of the repeating unit of PBC is 300-600.

6. The polyglycolic acid composite material according to claim 1, characterized in that: The melt index of PLA is less than 20 g / 10 min (190°C, 2.16 kg), preferably 0.7 to 6 g / 10 min; The degree of polymerization of the repeating unit of PLA is 300-600.

7. The polyglycolic acid composite material according to claim 1, characterized in that: The additives include one, two or more of a heat stabilizer, an antioxidant, an opener and a chain extender.

8. The polyglycolic acid composite material according to claim 7, characterized in that: The heat stabilizer is a phosphite heat stabilizer, preferably one or more of triphenyl phosphite, trimethyl phosphite and ethyl phosphite; Based on the total mass of PGA, PBC and PLA, the mass content of the heat stabilizer is 0.01-3%, preferably 0.05-1%.

9. The polyglycolic acid composite material according to claim 7, characterized in that: The antioxidant is a hindered phenol antioxidant, preferably one or more of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] pentaerythritol ester, N,N-1,6-hexylene-bis-[3,5-di-tert-butyl-4-hydroxyphenylpropionamide] and N,N-bis[β(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine; Based on the total mass of PGA, PBC and PLA, the mass content of the antioxidant is 0.01-3%, preferably 0.05-1%.

10. The polyglycolic acid composite material according to claim 7, characterized in that: The opening agent is oleamide and / or erucamide; Based on the total mass of PGA, PBC and PLA, the mass content of the opening agent is 0.01-3%, preferably 0.05-1%.

11. The polyglycolic acid composite material according to claim 1, characterized in that: The chain extender is one or more of diepoxide, dioximidazole, diisocyanate, polycarbodiimide, bisphthalimide, carboxylic anhydride, bicyclic imine ester, organosilazane, peroxide and diacyl dilactam; preferably, the chain extender is N,N-diepoxypropylbenzamide, hexamethylene diisocyanate, 1,2,4,5-benzenetetracarboxylic anhydride, phthalic anhydride, succinic anhydride, hexaphenyltrisilazane and N,N-oxalylbiscaprolactam, toluene diisocyanate, diphenylmethane diisocyanate, polymerized diphenyl One or more of 1,2-diisocyanate, 2,2,4-trimethylhexane diisocyanate, bis(phthalimide), benzoyl peroxide, diisopropyl peroxide, dibutyl peroxide, α,α-bis(tert-butylperoxy)diisopropylbenzene, 1,2,4,5-benzenetetracarboxylic dianhydride, bis(dioxazolone) or bis(benzoxazine), octamethylcyclotetrasilazane, hexaphenyltrisilazane and 2,2-bis(2-dioxazoline); Based on the total mass of PGA, PBC and PLA, the mass content of the chain extender is 0.01-5%, preferably 0.1-2%.

12. The method for preparing the polyglycolic acid composite material according to any one of claims 1 to 11, comprising the following steps: S1: mixing PGA, PBC, PLA, talc and additives to obtain a mixture; S2: Melting the mixture and extruding and granulating it to obtain the polyglycolic acid composite material.

13. The preparation method according to claim 12, characterized in that: In step S2, the mixture is melt-blended and extruded by a twin-screw extruder; Preferably, the temperature of the twin-screw extruder may be 190 to 250° C., preferably 210 to 240° C.; the rotation speed may be 30 to 500 r / min, preferably 70 to 200 r / min.

14. Use of the polyglycolic acid composite material according to any one of claims 1 to 11 or the polyglycolic acid composite material prepared by the preparation method according to claim 12 or 13 as a film material and an injection molding material.

Citation Information

Patent Citations

  • Preparation method and production process of full-biodegradable material

    CN113637297A

  • Film-forming material as well as preparation method and application thereof

    CN114702810A

  • Polyglycolic acid / polycarbonate composition, polyglycolic acid / polycarbonate material as well as preparation method and application of polyglycolic acid / polycarbonate material

    CN118085536A

  • Plasticized aliphatic polyester composition and its molding product

    JP1997137047A